USE OF MIXTURE DESIGN TO IMPROVE A TROPICAL MIXED FRUIT NECTAR - DE SOUSA, PAULO HENRIQUE MACHADO; RAMOS, AFONSO MOTA; DE BRITO, EDY SOUZA; MAIA, GERALDO ARRAES; DE AZEREDO, HENRIETTE MONTEIRO CORDEIRO; DO PRADO, GIOVANA MATIAS; GONZAGA, MARIA LEÔNIA DA COSTA (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2014)
This study aimed to develop beverages of mixed nectars of tropical fruits and to determine the best accepted formulation. The puree blend contents were: cashew apple (12.25-21.00 g 100 g-1); acerola (1.75-10.50 g 100 g-1); and mango (12.25-21.00 g 100 g-1), varying according to a mixture design. The evaluated responses were based on physicochemical, chemical and sensorial determinations. The models for antioxidant activity, overall acceptance, ascorbic acid content, phenolic content and viscosity were statistically signifi cant (P ≤ 0.05). The formulation with 12.25 g of cashew apple puree 100 g-1, 21.00 g of mango puree 100 g-1 and 1.75 g of acerola puree 100 g-1 was the best accepted by the tasters. Mango and cashew apple purees must be present in a greater proportion in the mixture, since they have high fl avour acceptance. The antioxidant activity of mixed nectars was most increased by acerola, followed by cashew apple. A high correlation was observed between antioxidant activity and acerola puree content and there was also a high correlation between antioxidant activity and both ascorbic acid and total phenolic contents.